Effects of silica coating and silane surface conditioning on the bond strength of rebonded metal and ceramic brackets - Saadet Atsü; Bülent Çatalbaş Ibrahim Erhan Gelgör (University of São Paulo, 2011)
OBJECTIVE: The aim of this study was to evaluate the effects of tribochemical silica coating and silane surface conditioning on the bond strength of rebonded metal and ceramic brackets. MATERIAL AND METHODS: Twenty debonded metal and 20 debonded ceramic brackets were randomly assigned to receive one of the following surface treatments (n=10 for each group): (1) sandblasting (control); (2) tribochemical silica coating combined with silane. Brackets were rebonded to the enamel surface on the labial and lingual sides of premolars with a light-polymerized resin composite. All specimens were stored in distilled water for 1 week and then thermocycled (5,000 cycles) between 5-55ºC. Shear bond strength values were measured using a universal testing machine. Student's t-test was used to compare the data (α=0.05). Failure mode was assessed using a stereomicroscope, and the treated and non-treated bracket surfaces were observed by scanning electron microscopy. RESULTS: Rebonded ceramic brackets treated with silica coating followed by silanization had significantly greater bond strength values (17.7±4.4 MPa) than the sandblasting group (2.4±0.8 MPa, P<0.001). No significant difference was observed between the rebonded metal brackets treated with silica coating with silanization (15±3.9 MPa) and the sandblasted brackets (13.6±3.9 MPa). Treated rebonded ceramic specimens primarily exhibited cohesive failure in resin and adhesive failure at the enamel-adhesive interface. CONCLUSIONS: In comparison to sandblasting, silica coating with aluminum trioxide particles followed by silanization resulted in higher bond strengths of rebonded ceramic brackets.